Political connection heterogeneity and corporate innovation - Rui Zhang; Zhengling Xiong; Honghuan Li; Baijun Deng (Journal of Innovation & Knowledge (JIK), 2022)
This paper examines whether political connection heterogeneity plays a role in corporate innovation in a sample of all listed firms in China from 2008 to 2016. Our results show that connections with central government officials promote innovation, while connections with local government officials inhibit innovation. The nonconformity between the influence of federalism and that of the local authorities is associated with the personnel promotion and tenure requirements that induce differential innovation-promotion strategies. We use the Heckman two-stage estimation to address selection bias, and we adopt a setting as a quasi-natural experiment, leveraging the decrease in local GDP growth rates to abate endogeneity. Our results endure these econometric treatments and a series of robustness checks. In mechanism tests, we document evidence that the central government promotes corporate innovation by improving innovation efficiency, while the local government inhibits innovation by reducing both innovation inputs and efficiency. We also find that the effect is even larger on high-tech firms and that it can be mitigated by marketization.
Keywords: G38; O38; O31; 650; Corporate governance; Corporate innovation; Political connection; JEL classification: G34; Promotion tournament